URDU-THE SIGNIFICANCE OF QAṢAṢ AL-QURʾĀN ON HUMAN SOCIETY - Saira Jabaeen Malik (دی اسکالر)
Human life comes into being due to a social unit called family and a collection of many such units constitutes a unit called society. Social life organizes and disciplines the day to day affairs including educational, social and some other needs. The society frames rules and regulations and compels people to respect the rights of other people. In this regard Al-Quran narrates various stories about human social life with a view to educating and reforming human beings. These Quranic stories are intended to produce good sentiments about honouring guests, possessing tender feelings for near ones, patience, self-control, rights and duties, and self-sacrifice. In addition, there are other stories to discourage evils like waywardness, telling lies, deceiving in weights and measures, indecency, immodesty and other evil doings.